Impaired Fast Network Oscillations and Mitochondrial Dysfunction in a Mouse Model of Alpha-synucleinopathy (A30P). (1st May 2018) - Robson, Emma; Tweedy, Clare; Manzanza, Nelson; Taylor, John-Paul; Atkinson, Peter; Randall, Fiona; Reeve, Amy; Clowry, Gavin J.; LeBeau, Fiona E.N.
Highlights: Age-dependent impairment in hippocampal gamma frequency activity in A30P mice. Gamma oscillations in slices from A30P mice show greater sensitivity to rotenone. Age-dependent impairment in mitochondrial function in A30P. Abstract: Intracellular accumulation of alpha-synuclein (α-syn) is a key pathological process evident in Lewy body dementias (LBDs), including Parkinson's disease dementia (PDD) and dementia with Lewy bodies (DLB). LBD results in marked cognitive impairments and changes in cortical networks. To assess the impact of abnormal α-syn expression on cortical network oscillations relevant to cognitive function, we studied changes in fast beta/gamma network oscillations in the hippocampus in a mouse line that over-expresses human mutant α-syn (A30P). We found an age-dependent reduction in the power of the gamma (20–80 Hz) frequency oscillations in slices taken from mice aged 9–16 months (9+A30P), that was not present in either young 2–6 months old (2+A30P) mice, or in control mice at either age. The mitochondrial blockers potassium cyanide and rotenone both reduced network oscillations in a concentration-dependent manner in aged A30P mice and aged control mice but slices from A30P mice showed a greater reduction in the oscillations. Histochemical analysis showed an age-dependent reduction in cytochrome c oxidase (COX) activity, suggesting a mitochondrial dysfunction in the 9+A30P group. A deficit in COX IV expression was confirmed by immunohistochemistry. Overall, our data demonstrate an age-dependent impairment in mitochondrial function and gamma frequency activity associated with the abnormal expression of α-syn. These findings provide mechanistic insights into the consequences of over-expression of α-syn which might contribute to cognitive decline.